Biological peculiarities of a rare medicinal mushroom Fomitopsis officinalis (Fomitopsidaceae, Polyporales) on agar media and plant substrates - О. B. Mykchaylova; N. А. Bisko; М. М. Sukhomlyn; М. L. Lomberg; М. V. Pasaylyuk; М. М. Sukhomlyn; Y. V. Petrichuk; A. P. Gryganskyi (Regulatory Mechanisms in Biosystems, 2017)
Fomitopsis officinalis (Vill.) Bondartsev & Singer is a rare and endangered medicinal mushroom, known in medical practice as agarikon. Strain 5004 of F. officinalis from the IBK Mushroom Culture Collection of M. G. Kholodny Institute of Botany was verified using morphological and molecular genetic techniques. DNA analysis shows 99% identity of the investigated strain to other F. officinalis sequences deposited in NCBI databases. The results of the study of the biological characteristics of F. officinalis 5004 on agar nutrient media and plant substrates of various compositions are presented. We observed the microstructures of F. officinalis culture using light and scanning electron microscopy. The hyphae have regular unilateral clamp connections of two types: without a slit and rare medallion-type clamps, some anastomoses and mycelial cords as well as blastoconidia after prolonged cultivation (more than 30 days). The incrustation of the hyphae in the form of thin villi is revealed for the first time. The morphology of the mycelial colonies of F. officinalis depended on the composition of the nutrient medium. According to the radial growth rate the culture of investigated species belongs to the fungi growing very slowly within 0.4–1.9 mm/day. The fastest growth of F. officinalis 5004 was observed on malt agar with the addition of larch sawdust: 1.8 ± 0.1 mm/day. The critical temperature for mycelial growth was 41 ± 0.1 ºC. We tried three variants of plant substrates for fructification: sunflower husk, larch sawdust and larch chips. The substrate composition influenced the vegetative growth and the formation of teleomorph stage. The sunflower husk was the most favorable substrate for the growth of vegetative mycelium. The mycelium had completely colonized this substrate by the 30th day, in contrast to the larch chips, which were only partially colonized (ca. 50%) on 30–40th days of experiment. The fungus developed fruit bodies on both substrates: the sunflower husk and larch chips. The least suitable substrate for vegetative growth of this species was the larch sawdust. After two months of incubation, the mycelium covered only 27% of the visible surface of substrate blocks, with no primordia and fruiting bodies forming. Thus, the obtained mycelium growth parameters on nutrient media, micro- and macromorphological characteristics can be used as additional taxonomic characteristics of F. officinalis culture in the vegetative stage of growth. The strain ІBK 5004 may become a potential producer for new fungal biotechnologies in Ukraine in the near future.